2015
DOI: 10.1017/s0950268815002666
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variations of risk factors associated with HCV infection in drug users in southwestern China

Abstract: Hepatitis C virus (HCV) has become a global public health problem. Many studies have been conducted to identify risk factors for HCV infection. However, some of these studies reported inconsistent results. Using data collected from 11 methadone clinics, we fit both a non-spatial logistical regression and a geographically weighted logistic regression to analyse the association between HCV infection and some factors at the individual level. This study enrolled 5401 patients with 30·0% HCV infection prevalence. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition, the prevalence of HCV antibody was five times higher among participants of Vietnamese ethnic origin. Although ethnicity has been reported to be associated with HCV in other studies [39], we suggest that this is likely to be a proxy indicator of other structural risk behavioral or other risk factors, which would need to be further investigated in our context.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the prevalence of HCV antibody was five times higher among participants of Vietnamese ethnic origin. Although ethnicity has been reported to be associated with HCV in other studies [39], we suggest that this is likely to be a proxy indicator of other structural risk behavioral or other risk factors, which would need to be further investigated in our context.…”
Section: Discussionmentioning
confidence: 94%
“…A previous study found that healthcare access in ethnic minority regions was worse than in the non-minority region ( Mali Xia et al, 2014 ; Wang and Pan, 2016 ). Some ethnic minorities, located in border areas, may have more drug trafficking and use, potentially contributing to the high incidence rate of HCV infection ( Zhou et al, 2016 ). Besides, the governments in developed areas may invest more money and resources in healthcare and people’s health awareness than in underdeveloped areas ( Zhou and Zhou, 2013 ).…”
Section: Epidemiological Characteristics Of Hepatitis C In the Mainla...mentioning
confidence: 99%
“…17 and Zhou et al . 18 . However, there is no a similar logistic regression model to deal with those disease detection data and considering both the geographical and temporal variation of the correlation.…”
Section: Introductionmentioning
confidence: 99%